Body Dysmorphic Disorder: a Guide to Identification and Management for the General Dental Practitioner. (2nd April 2020) - Rosten, Adina; Newton, Tim
Abstract : Body Dysmorphic Disorder (BDD) is a relatively common psychiatric condition in which the individual is disproportionately concerned about an aspect of his/her appearance. People with BDD are highly likely to seek cosmetic dental treatment. However, the provision of such treatment is contra-indicated. This article will identify simple techniques for practitioners to screen for and manage patients with BDD. CPD/Clinical Relevance: This article addresses the management of patients with a specific psychiatric illness who are likely to present for cosmetic dental treatments.